2016
DOI: 10.1242/jcs.169011
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PPARγ in endothelial cells leads to impaired angiogenesis

Abstract: Tie2-promoter-mediated loss of peroxisome proliferator-activated receptor gamma (PPARγ, also known as PPARG) in mice leads to osteopetrosis and pulmonary arterial hypertension. Vascular disease is associated with loss of PPARγ in pulmonary microvascular endothelial cells (PMVEC); we evaluated the role of PPARγ in PMVEC functions, such as angiogenesis and migration. The role of PPARγ in angiogenesis was evaluated in Tie2CrePPARγ flox/flox and wild-type mice, and in mouse and human PMVECs. RNA sequencing and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 76 publications
0
37
0
Order By: Relevance
“…We and others showed that PPARγ promotes endothelial survival and regeneration (Alastalo et al, 2011; Vattulainen-Collanus et al, 2016). In a transgenic mouse with deficient endothelial PPARγ, pulmonary hypertension and adverse vascular remodeling did not reverse following re-exposure to room air after chronic hypoxia (Guignabert et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We and others showed that PPARγ promotes endothelial survival and regeneration (Alastalo et al, 2011; Vattulainen-Collanus et al, 2016). In a transgenic mouse with deficient endothelial PPARγ, pulmonary hypertension and adverse vascular remodeling did not reverse following re-exposure to room air after chronic hypoxia (Guignabert et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…PPARG is involved in neuronal development, inflammation, keratinocyte differentiation, and epidermal barrier recovery . In addition, PPARG contributes to lung maturation and to pulmonary angiogenesis . Concordantly, PPARGC1 activates vascular endothelial growth factor expression VEGF and is important for angiogenesis and neovascularization .…”
Section: Discussionmentioning
confidence: 99%
“…* P < 0.05; ** P < 0.01; *** P < 0.001. of nuclear receptors, has been proved to ameliorate PAH by inhibiting PASMCs proliferation, improving ECs function, alleviating inflammation, etc. [11][12][13][14] In this experiment, the direct effect of PPARγ on RV was examined.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Accumulating evidence demonstrated that activation of PPARγ may be a novel PAH therapeutic target. 10) PPARγ agonist rosiglitazone (Rosi) has been proved to alleviate PAH in rats, including regulating endothelial dysfunction, 11) sustaining angiogenic potential in mature pulmonary microvascular endotheliai cells (PMVECs), 12) preventing PASMCs proliferation, 13,14) etc. However, the mechanisms of PPARγ's effect on PAH-induced RVF remain unknown.…”
mentioning
confidence: 99%